2008
DOI: 10.1111/j.1365-2788.2007.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural characteristics associated with dementia assessment referrals in adults with Down syndrome

Abstract: The behavioural differences between those referred and the comparison group suggest that two factors are involved in the instigation of a referral for a dementia assessment: the nature of the behavioural presentation (excesses rather than deficits) and the effect of that behavioural change upon the care staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 36 publications
2
51
0
1
Order By: Relevance
“…Currently, treatment options are limited: in the few randomized controlled trials in the DS population, effectiveness of donepezil and memantine was not proven [13]. Alternatively, contemporary intellectual disability care focuses on timely (non-)pharmacologic therapy to reduce behavioral and psychological symptoms of dementia—the major cause of referral [14]—to improve quality of life and reduce caregiver burden [10], [15]. Although the process of neurodegeneration cannot yet be prevented or stopped, a recently completed clinical trial (phase Ib) using immunotherapy with aducanumab reported a dose- and time-dependent reduction of Aβ plaques in the brain of patients with prodromal or mild AD, indicating the potential of this human monoclonal antibody as disease-modifying strategy for AD [16].…”
Section: Introduction: Down Syndrome At High Risk For Alzheimer's Dismentioning
confidence: 99%
“…Currently, treatment options are limited: in the few randomized controlled trials in the DS population, effectiveness of donepezil and memantine was not proven [13]. Alternatively, contemporary intellectual disability care focuses on timely (non-)pharmacologic therapy to reduce behavioral and psychological symptoms of dementia—the major cause of referral [14]—to improve quality of life and reduce caregiver burden [10], [15]. Although the process of neurodegeneration cannot yet be prevented or stopped, a recently completed clinical trial (phase Ib) using immunotherapy with aducanumab reported a dose- and time-dependent reduction of Aβ plaques in the brain of patients with prodromal or mild AD, indicating the potential of this human monoclonal antibody as disease-modifying strategy for AD [16].…”
Section: Introduction: Down Syndrome At High Risk For Alzheimer's Dismentioning
confidence: 99%
“…wandering) are evident in the course of dementia with the latter more likely to lead to referral (Urv et al . 2003; Adams et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
“…17 Fortunately, adults with DS are at lower risk for psychosis compared with those with other intellectual disabilities. 18 Use of private speech, or "self-talk," has at times been interpreted as psychosis but is not and should be viewed as adaptive communication for adults with DS.…”
Section: Mental Healthmentioning
confidence: 99%
“…18 Caregiver input is essential in gathering comprehensive data on baseline behavior for comparison with noted changes. 17 Behavioral and personality changes may in fact precede a deterioration of memory as frontal lobe function may be first to be affected in DS patients with dementia. 20 Positive personality traits associated with DS include an engaging and pleasant manner that may shift to aggressive or withdrawn behavior with AD.…”
Section: Mental Healthmentioning
confidence: 99%